Technical communication pedagogical model for an industry-based curriculum in Malaysian vocational colleges / Khairul Azhar Jamaludin - Khairul Azhar , Jamaludin (2019)
Poor interaction between Technical and Vocational Education and Training (TVET) curriculum developers, instructors and industry in designing a sound curriculum has resulted in poor mastery of communication-for-work skills among TVET graduates. Consequently, this situation has affected their employability. Developing technical communication is beneficial in equipping students with communication skills that are valued by their future employers in the industry. Hence, this study is to develop technical communication pedagogical model (TCPM) for an industry-based curriculum in Malaysian Vocational Colleges, based on three research objectives: a) to identify the key determinants of TCPM for Malaysian Vocational Colleges from industry and TVET experts’ perspectives, b) to propose TCPM for Malaysian Vocational Colleges and c) to evaluate the effect of English language proficiency on the development of TCPM for Malaysian Vocational Colleges. This study employs fuzzy the delphi method (FDM) to identify the key determinants of TCPM and a survey design with the Partial Least Square-Structural Equation Modeling (PLS-SEM) analysis to develop the model. In the initial phase, 17 experts from local TVET institutions and industry were selected for the FDM. Generally, the panel of experts agreed that the objective of TCPM should focus on guiding English language instructors in developing relevant technical communication skills and ensuring the learning environment is conducted parallel to the concept of an industry-based curriculum. The content of learning should focus on developing oral technical communication, written technical communication, interpersonal and researching skills. In addition, the method of delivery should focus on providing authentic learning activities that allow students to apply technical communication. For assessment method, evaluation can be conducted through observations on students’ communicative experiences in an authentic setting, presentations and terminology exams. The experts also agreed that the ability to comprehend information, and apply accurate sentence structure, verbal strategy and grammar in conversation are important for technical communication skills development. From these findings, a survey questionnaire is developed and administered on 205 English language instructors in Vocational Colleges across six zones (Northern, Central, Southern, East Coast, Sabah and Sarawak) in Malaysia using random stratified sampling method. The data is analyzed using the PLS-SEM, SmartPLS. Overall, all constructs have a positive and significant effect on perceived importance of TCPM (Objective: p=0.012, t=2.249, Content of Learning: p=0.032, t=1.852, Assessment Method: p=0.000, t=4.196), except for Method of Delivery (p=0.301, t=0.522). The level of coefficient of determination is found to be moderate (R2=0.526). The result of effect size (f2) analysis indicates that all constructs have a small effect size (Objective: f2=0.032, Content of Learning: f2=0.027, Assessment Method: f2=0.116), except for Method of Delivery with effect size of 0.002. The model has also achieved acceptable predictive relevance (Q2=0.316). For mediation analysis, it is found that perceived importance of English language proficiency is a complementary partial mediator for Content of Learning and Assessment Method construct. In short, the proposed TCPM can be a reference in implementing technical communication in Malaysian Vocational Colleges, as it has considered the professional opinions of various industry experts, TVET experts and English language instructors.